Mastering Autodesk Inventor 2010 - Waguespack, Curtis, 1974-; Jahraus, Loren; Safari eBooks (Indianapolis, Ind. : Wiley Pub., 2009)
"Used to design everything from airplanes to appliances, Autodesk Inventor is the industry-leading 3D mechanical design software. This detailed tutorial and reference covers practical applications to help you solve design problems in your own work environment, allowing you to do more with less. It also addresses topics that are often omitted from other guides, such as Inventor Professional modules, design tactics for large assemblies, using 2D and 3D data from other CAD systems, and a detailed overview of the Inventor utility tools such as Design Assistant and Task Scheduler that you didn't even know you had"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Engineering graphics; Engineering models -- Data processing; Autodesk Inventor (Electronic resource); Electronic books